The Influence of Provincial Minimum Wages and Education on Changes in Worker Status in Lampung Province - Dea Pitri Dayanti; Ida Budiarty (International Journal of Economics and Management Sciences, 2025)
This study investigates the influence of the Provincial Minimum Wage (MW) and education level on changes in worker status in Lampung Province, using Gross Domestic Regional Product (GDRP) as a control variable. Changes in worker status are defined as individual transitions in the labor market from 2021 to 2022, numerically coded as follows: employed-to-employed (3), employed-to-unemployed (1), unemployed-to-employed (2), and unemployed-to-unemployed (0). The analysis uses microdata from the National Labor Force Survey (NLFS), consisting of 22,999 respondents across all regencies/cities in Lampung Province. This study uses VAR and VECM models to examine short and long term relationships among the variables. The findings reveal that the minimum wage (LOGMWt) does not significantly influence changes in worker status in either the short or long term. Education shows varied effects: lower (EDUC1) and higher (EDUC3) levels have a significant negative impact, while middle education (EDUC2) has a significant positive effect. Meanwhile, LOGGDRP positively and significantly affects worker status changes in both time frames. These results underscore that improvements in EDUC2 and LOGPDRB play a more in facilitating labor market transitions than minimum wage policy alone.